2020
DOI: 10.1080/15428052.2020.1824833
|View full text |Cite
|
Sign up to set email alerts
|

Food Perception and Aesthetics - Linking Sensory Science to Culinary Practice

Abstract: This systematic overview tries to link scientific knowledge on human perception and appreciation mechanisms to culinary practices. We discuss the roles of the human senses during eating, starting out with basic mechanisms of taste and smell perception, up to principles of aesthetics. These insights are related to how foods are experienced, how ingredients are combined, the use of flavor bases in cuisines, the creation of a full course meal, the choice of a beverage with a dish, and how people learn to apprecia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 134 publications
(140 reference statements)
1
16
0
Order By: Relevance
“…Peppermint may thus, in addition to activating the olfactory 10.3389/fnbeh.2022.941517 nerve, have activated the facial and glossopharyngeal nerve (taste innervation of the tongue), resulting in the licking and biting behavior. For the young group of horses naïve to mints, this could indicate that these may have been able to link smell with taste (as, e.g., humans, Schifferstein et al, 2020), which has never been demonstrated before (Rørvang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Peppermint may thus, in addition to activating the olfactory 10.3389/fnbeh.2022.941517 nerve, have activated the facial and glossopharyngeal nerve (taste innervation of the tongue), resulting in the licking and biting behavior. For the young group of horses naïve to mints, this could indicate that these may have been able to link smell with taste (as, e.g., humans, Schifferstein et al, 2020), which has never been demonstrated before (Rørvang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This rock art shows a human figure accessing a nest of bees at some height above the ground while several bees fly around (Ransome, 2004). The artistic representation is potentially instructional, and shows a connection between bees and humans that was so important as to risk one's life to collect prized food in the form of honey that produced a pleasant sensory taste experience and had healing benefits (Boukraâ, 2019;Schifferstein et al, 2020). There is evidence that honey from both honeybees (Apis spp.)…”
Section: Bees In Antiquitymentioning
confidence: 99%
“…As evidenced by the scant number of papers, recent research on tourism aesthetics has been relatively weak in relation to other tourism research and has focused on the ecological service value of tourism [ 16 ] and its cultural ecosystem service value [ 17 ]. Existing tourism aesthetic studies focus primarily on natural landscape aesthetics [ 18 ], music [ 19 ], photographs [ 20 ], Chinese gardens [ 21 ], sculptures [ 22 ], calligraphy art [ 23 ], architecture [ 24 ], food [ 25 , 26 ], and the tourism experience [ 27 ], while tourism crafts are not considered. Regarding the subject of tourism aesthetics, it mainly studies aesthetic education [ 28 ], aesthetic preference [ 29 ], aesthetic appreciation [ 30 ], and aesthetic experience [ 31 ], and it incorporates the content of aesthetic emotion [ 32 ] and psychological consciousness of aesthetics from the tourists’ perspective [ 33 ].…”
Section: Introduction and Literaturementioning
confidence: 99%